Oxyberberine, a novel HO-1 agonist, effectively ameliorates oxidative stress and inflammatory response in LPS/D-GalN induced acute liver injury mice via coactivating erythrocyte metabolism and Nrf2 signaling pathway. (August 2022) - Ai, Gaoxiang; Wu, Xiaoyan; Dou, Yaoxing; Huang, Ronglei; Zhong, Linjiang; Liu, Yuhong; Xian, Yanfang; Lin, Zhixiu; Li, Yucui; Su, Ziren; Chen, Jiannan; Qu, Chang
Abstract: Oxyberberine (OBB), a main gut-mediated metabolite of Phellodendron chinense Cortex (PC), exhibits prominent protective property against acute liver injury (ALI). Heme oxygenase-1 (HO-1) is a vital molecule in attenuating acute and chronic liver injury for its prominent anti-oxidative injury and anti-inflammation properties. The present study was performed to investigate the hepatoprotective role of OBB through HO-1 signaling pathway in lipopolysaccharide/D-galactosamine (LPS/D-GalN) induced ALI. Our results indicated that PC treatment improved survival rate and its metabolite OBB evidently improved histopathological deteriorations and liver function. Additionally, OBB dramatically ameliorated hepatic oxidative stress and inflammation. Besides, OBB exerted remarkable HO-1 agonistic activity, even be comparable to hemin (a HO-1 inducer), as evidenced by increased HO-1 level, carbon monoxide and bilirubin activities, which are the markers of erythrocyte metabolism. Moreover, OBB modulated the parameters of inflammation and oxidative stress through HO-1 dependent pathway. Beyond this, OBB also notably suppressed the translocation of p65, enhanced antioxidation defense genes expressions, promoted the degradation of Kelch-like ECH-associated protein 1 (Keap1) and the nuclear translocation of nuclear factor-erythroid-2-related factor 2 (Nrf2). In conclusion, OBB could be the principle active metabolite substance of PC and exert excellent hepatoprotective effects via inducing HO-1 through coactivation of erythrocyte metabolism and Nrf2/HO-1 pathway. Highlights: OBB is a novel gut microbiota-mediated oxidative metabolite of PC. OBB inhibited oxidative stress and inflammatory response in ALI mice as HO-1 agonist. OBB coactivated the erythrocyte metabolism and Nrf2/HO-1 pathway as HO-1 agonist. OBB has potential to be exploited as a promising candidate for ALI treatment.